Relationship between teachers' perceptions towards school principals' instructional leadership practices and teachers' concerns about teaching and learning innovation - Mohd Yunus, Laila Manja; Abdullah, Arnida; Jusoh, Rosnani (Human Resource Management Academic Research Society, 2019)
The purpose of this study is to determine the relationships between secondary school teachers perceptions towards instructional leadership practices of their principals and teachers concern about teaching and learning innovation. The sample of the study consists of 350 secondary school teachers in Petaling Perdana, Selangor. The instruments were adapted from the The Principal Instructional Management Rating Scale (PIMRS) developed by Hallinger and Murphy (1985) and Stages of Concern Questionnaire (SoCQ) developed by Hall and Hord (2011). Descriptive and inferential analyses were performed to examine the relationship including frequencies, percentage, standard deviation and correlation. Data analysis indicated that there was a moderate positive correlation between teachers perceptions towards the school principal instructional leadership style and teachers concerns about teaching and learning innovation with values of r = 0.371 ** and sig 0.00 (p?0.01). A weak relationship was found in the dimension of instructional leader's role in defining a school mission. This indicates that the principals have implemented defining a school mission dimension at weak level and significant. The finding should be given serious attention with some improvement that can be made to optimise the teachers’ concerns about teaching and learning innovation.